Cu2ZnSnSe4 thin-film solar cells fabricated using Cu2SnSe3 and ZnSe bilayers. (23rd March 2015) - Kim, Kang Min; Liao, Kuang Hsiang; Tampo, Hitoshi; Shibata, Hajime; Niki, Shigeru
Abstract: Evaporated Cu2 SnSe3 (CTSe) and ZnSe bilayers are used as precursors for the fabrication of Cu2 ZnSnSe4 (CZTSe) thin films. Large grains (i.e., >1 µm) in CZTSe were obtained at a relatively low annealing temperature of 500 °C. The stacking order of precursors strongly affected the chemical composition of CZTSe thin films even under identical growth conditions. Zn loss in CTSe/ZnSe/Mo precursors occurred during CTSe deposition, whereas ZnSe/CTSe/Mo precursors showed improved stability in composition. The CZTSe solar cells fabricated using ZnSe/CTSe bilayer precursors with annealing showed a conversion efficiency of over 7%.